Biyoteknolojinin transhümanizm ve evrim bağlamındaki yeri : insan genom projesi ve etik tartışmalar - Akçay, Elif (My University, 2020)
İnsanlığın dünyayı anlama ve etrafını keşfetme uğraşı yüzyıllardır devam etmektedir. Bu uğraş insan bedeninin keşfi ve biyoloji ile öze yönelirken en büyük yardımcısı da gelişen teknoloji olmaktadır. Bilişim ve teknolojinin hâkim olduğu dünyamızda insanların kendi yarattığı biyoteknolojik sorunlarla başa çıkmaya çalıştığı görülmektedir. Bu tezin konusu biyoteknolojinin transhümanizm ve evrim bağlamındaki yeri, İnsan Genom Projesi ve beraberinde gelişen genetik mühendisliği, CRISPR-Cas9 teknolojisi ve etik tartışmalardır. Bu konunun araştırılmasındaki amaç ise gelişen teknolojinin insan hayatlarından ziyade artık insan bedenine daha fazla etki etmesi ve bu durumun yeterince tartışılmamasıdır. Olumlu ya da olumsuz çok büyük etkileri olacağı belli olan bu konu hakkında özellikle sosyal bilimler araştırmaları ve literatürdeki eksiklik dikkat çekmiştir. Araştırmanın hedefi bu eksikliği giderecek, kaynak olacak, genel kapsamlı bir derleme ortaya koymaktır.Araştırmada nitel araştırma yöntemlerinden literatür taraması kullanılmıştır. Analitik bir çalışma olan bu tez de insanın teknolojiyi nasıl şekillendirdiğinden çok, teknolojinin insana nasıl şekil vermeye başladığı gözler önüne serilmiştir. Geçmişteki devrimlerden çok daha hızlı içine sürüklendiğimiz bu biyoteknoloji devriminin olası sonuçları, sadece yaşayan kuşağı etkilemekle kalmayıp sonraki tüm nesillerin tamamını da etkileyeceğini öngörmektedir.Araştırmada biyoteknoloji aracılığı ile insan değişiminin getireceği belli etik sorunlar ele alınmıştır. Biyoteknolojinin sosyal çıktıları ve etkilerinin yer aldığı bu tez ayrıca biyoetiğin, etik ve uygulamalı felsefe aracılığıyla sadece akademi içinde kalmayıp gündelik yaşamda da yer bulmasını hedeflemiştir.

The effort of humanity to understand the world and to discover its surroundings has been going on for centuries. While this struggle is directed towards the essence with the discovery of the human body and biology, its biggest help is the developing technology. It is seen that in our world where information and technology is dominant, people are trying to deal with the biotechnological problems created by them.The subject of this thesis is the place of biotechnology in the context of transhumanism and evolution, the Human Genome Project and the accompanying genetic engineering, CRISPR-Cas9 technology and ethical discussions. The aim of researching this issue is that developing technology has more impact on the human body than on human lives and this situation is not discussed enough. On this subject, which has obviously positive or negative effects, the social sciences research and the lack of literature are noteworthy. The aim of the research is to provide a general and comprehensive review that will compensate for this shortcoming.In the research, a literature review, one of the qualitative research methods, was used. In this thesis, which is an analytical study, it is revealed how technology began to shape people rather than how it shapes technology. The possible consequences of this biotechnology revolution, which we have been dragged into much faster than the previous revolutions, predicts that it will not only affect the living belt, but also all subsequent generations.In the research, certain ethical problems that human change will bring through biotechnology are discussed. This thesis, which includes the social outcomes and effects of biotechnology, also aims to make bioethics find a place in daily life, not only within the academy through ethical and applied philosophy.
Keywords: a literature review; also aims to make bioethics find a place in daily life; Bilişim teknolojisi; Biotechnology; Biyoetik; Biyoteknoloji; but also all subsequent generations.In the research; certain ethical problems that human change will bring through biotechnology are discussed; CRISPR-Cas9 technology and ethical discussions; CRISPR-Cas9 Teknolojisi; Etik; Evrim; Gazetecilik; In this thesis; Information technology; It is seen that in our world where information and technology is dominant; İnsan Genom Projesi; it is revealed how technology began to shape people rather than how it shapes technology; its biggest help is the developing technology; Journalism; not only within the academy through ethical and applied philosophy; On this subject; one of the qualitative research methods; people are trying to deal with the biotechnological problems created by them.The subject of this thesis is the place of biotechnology in the context of transhumanism and evolution; predicts that it will not only affect the living belt; The aim of researching this issue is that developing technology has more impact on the human body than on human lives and this situation is not discussed enough; The aim of the research is to provide a general and comprehensive review that will compensate for this shortcoming.In the research; The effort of humanity to understand the world and to discover its surroundings has been going on for centuries; the Human Genome Project and the accompanying genetic engineering; The possible consequences of this biotechnology revolution; the social sciences research and the lack of literature are noteworthy; This thesis; Transhümanizm; was used; which has obviously positive or negative effects; which includes the social outcomes and effects of biotechnology; which is an analytical study; which we have been dragged into much faster than the previous revolutions; While this struggle is directed towards the essence with the discovery of the human body and biology